2021
DOI: 10.3389/fonc.2021.676562
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Metabolism as Inductor of Epigenetic Changes in Breast Cancer: Therapeutic Opportunities

Abstract: Aberrant metabolism is arising interest in the scientific community not only because of the role it plays in the development and establishment of the tumor mass but also the possibility of drug poisoning of key enzymes overexpressed in tumor cells. Moreover, tumor metabolism provides key molecules to maintain the epigenetic changes that are also an undisputed characteristic of each tumor type. This metabolic change includes the Warburg effect and alterations in key pathways involved in glutaminolysis, pentose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
(80 reference statements)
1
7
0
Order By: Relevance
“…Recent research reports that the aberrant metabolism in cancer is not only involved in maintaining a high proliferative rate or survival but also has consequences that impact epigenetic mechanisms such as DNA methylation, histone post‐translational modifications, triggering oncogenes activation or loss of tumor suppressor genes expression resulting in tumor development 53 . In the current study, UA significantly blocked the Pten KO‐regulated pyruvate metabolic metabolites including pyruvate and lactate (Figure 5B) which are highly linked with the basic epigenetic machinery 54,55 . Advances in the understanding of prostate cancer metabolism might help to explain many of the biological responses such as epigenetic modulations that are induced by treatment, which might, in turn, lead to the attainment of more effective therapeutic effects.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Recent research reports that the aberrant metabolism in cancer is not only involved in maintaining a high proliferative rate or survival but also has consequences that impact epigenetic mechanisms such as DNA methylation, histone post‐translational modifications, triggering oncogenes activation or loss of tumor suppressor genes expression resulting in tumor development 53 . In the current study, UA significantly blocked the Pten KO‐regulated pyruvate metabolic metabolites including pyruvate and lactate (Figure 5B) which are highly linked with the basic epigenetic machinery 54,55 . Advances in the understanding of prostate cancer metabolism might help to explain many of the biological responses such as epigenetic modulations that are induced by treatment, which might, in turn, lead to the attainment of more effective therapeutic effects.…”
Section: Resultssupporting
confidence: 51%
“…53 In the current study, UA significantly blocked the Pten KO-regulated pyruvate metabolic metabolites including pyruvate and lactate (Figure 5B) which are highly linked with the basic epigenetic machinery. 54,55 Advances in the understanding of prostate cancer metabolism might help to explain many of the biological responses such as epigenetic modulations that are induced by treatment, which might, in turn, lead to the attainment of more effective therapeutic effects.…”
Section: Pten Ko and Ua Regulate Epigenetics And Pca Via Cellular Met...mentioning
confidence: 99%
“…Another possibility is that changes in translational dysregulation may affect specific molecular or cellular processes that contribute to cancer initiation and progression 66,67 . Studies have demonstrated that aberrant protein synthesis leads to changes in the expression of specific genes by affecting chromatin dynamics via epigenetic mechanisms 68,69 . These findings align with the recognized role of CDK8 in the Mediator complex, suggesting that CDK8 cooperates with MYC or other transcription factors to modulate transcriptional regulation, chromatin modifications, and the overall chromatin landscape, thereby impacting gene expression and crucial cellular processes essential for development, stability, and disease states, such as cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, transgenic mice overexpressing G6PDH have been found to exhibit an extended lifespan, which has been attributed to increased NADPH levels. Furthermore, reducing the expression of the tumor suppressor gene ataxia-telangiectasia mutated (ATM) can restore glucose flux throughout the PPP, enabling cells to overcome senescence (174)(175)(176)(177). These studies underscore the significance of the PPP in providing NADPH and maintaining redox balance during cellular senescence.…”
Section: The Ppp In Cellular Senescencementioning
confidence: 99%